PERLINDUNGAN HUKUM TERHADAP JUSTICE COLLABORATOR DALAM TINDAK PIDANA PEMBUNUHAN BERENCANA - Mus, Arif Dermawan; Soeskandi, Hari (Gapenas Publisher, 2023)
Justice Collaborator basically has the meaning of giving a term to someone who commits a crime that cooperates with law enforcement officials to uncover the veil of crimes he knows. The issue of justice collaborator is also contained in Law 13/2014 concerning the Second Amendment of Law 13/2006 concerning the Protection of Witnesses and Victims. The protection of justice collaborator is an inherent right for witnesses and victims who assist investigations in criminal acts, especially in the crime of murder. However, the protection of justice collaborators, especially in murder, is not thoroughly regulated by the law a quo, so there is a legal vacuum. The formulation of the problem imposed in this case is what is the form of legal protection of justice collaborators in the crime of premeditated murder. Witnesses and victims who become justice collaborators are also entitled to a form of legal protection, a person or legal subject who is a witness in a premeditated murder crime or even someone who is a witness and involved in a criminal act is certainly entitled to legal protection guarantees. In this case, what is meant is not only at the time of the case but also the guarantee of a safe life, so that the guarantee will also be guaranteed by the LPSK as the institution entitled in that regard. There are 2 (two) forms of legal protection for justice collaborators in premeditated murder. Among others, preventive legal protection, namely physical and psychological protection, legal protection, special handling, awarding. Meanwhile, the form of repressive protection for criminal offenders in the event of premeditated murder can apply to the LPSK in accordance with the provisions of Number 9 SEMA 4/2011